Archaeological Perspectives of Warfare on the Great Plains - Clark, Andrew J.; Bamforth, Douglas B. (University Press of Colorado, 2018)
The Great Plains of the United States have played an influential role in shaping academic and popular visions of Native American warfare, largely because of the well-documented violence that was so central to the expansion of Euroamerican settlement there. However, violence has deep roots on the Plains, and these roots have never been examined systematically across the region as a whole. Covering the Plains as well as some adjacent areas and spanning both pre-Contact and post-Contact periods, this volume explores a series of central topics that are important regionally and to the larger study of warfare in general. The editors provide an overview of the evidence for violence in the region as a whole, but contributors focus particularly on three important and interrelated topics: what fortifications tell us about war, what representations of war in art tell us about combatants' views of war, and how war shaped and reflected human societies on the Plains.
Description based on print version record.
KU Select 2017: Front list Collection
Keywords: Social Science / Archaeology; Social sciences; Electronic books